2012
DOI: 10.5762/kais.2012.13.6.2600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulation-Based Training on the Clinical Competence and Confidence of Nursing Students in Intravenous Injection Performance and the Satisfaction of Clients

Abstract: Purpose: This study was conducted to examine the effect of simulation-based training on the clinical competence and confidence of nursing students in intravenous injection performance and the satisfaction of clients. Methods: This study employed a randomized control posttest non-synchronized design. The participants were 90 second-year nursing students(31 multimedia group, 28 IV model group, 31 IV computerized systems group) of S-University in Seoul, Korea. Each group was given 30 minutes for five trial inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
1
4
0
1
Order By: Relevance
“…There was no significant difference in clinical reasoning capacity in nursing care for respiratory infectious disease. The results are consistent with the study of Kang and Kang (2020). However, there was no statistically significant differences between two groups in this study.…”
Section: Discussionsupporting
confidence: 92%
“…There was no significant difference in clinical reasoning capacity in nursing care for respiratory infectious disease. The results are consistent with the study of Kang and Kang (2020). However, there was no statistically significant differences between two groups in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The study is significant in the sense that it employed VRS for an IV injection training system, and it was applied as a substitution method to improve the nursing competency of nursing students by implementing a VR training system, wherein the environment was similar to that in a clinical setting. Most practicum training for IV catheter injection using VR involves using the VR-haptic IV simulator (VR simulator), and most studies compare the differences among the training groups using a VR simulator and IV arm simulator [16]. Training with the IV arm simulator was reported to be more effective as it allowed the students to learn skills, such as IV catheter insertion [8].…”
Section: Discussionmentioning
confidence: 99%
“…Training with the IV arm simulator was reported to be more effective as it allowed the students to learn skills, such as IV catheter insertion [8]. Conversely, some studies reported that the VR simulator was more effective for improving clinical practice competencies than the IV arm simulator [8,16]. A study that was conducted to address the limitation of such previous studies applied a combination of the two types of simulators and determined that the group using the combination of the two simulators had higher levels of clinical practice competencies than those who used each simulator individually [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifting-thrusting range and frequency are set by software used, the motor moves the needle in to tissue model, and the sensor attached to the needle holder measures the needle-tissue interaction force. 진다 [1][2][3] . 특히 기초 실습이 부족한 경우 학생들의 불안감이 높다는 보고도 있어 4) , 체계적이고 표준화된 의학 실습 교육이 강조되고 있다.…”
unclassified